2018
DOI: 10.3389/fnbot.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

Improving Fine Control of Grasping Force during Hand–Object Interactions for a Soft Synergy-Inspired Myoelectric Prosthetic Hand

Abstract: The concept of postural synergies of the human hand has been shown to potentially reduce complexity in the neuromuscular control of grasping. By merging this concept with soft robotics approaches, a multi degrees of freedom soft-synergy prosthetic hand [SoftHand-Pro (SHP)] was created. The mechanical innovation of the SHP enables adaptive and robust functional grasps with simple and intuitive myoelectric control from only two surface electromyogram (sEMG) channels. However, the current myoelectric controller h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…Grip performances of the "KIT Prosthetic Hand" were evaluated by using split cylinders with diameters of 31 mm and 49 mm, containing a six degrees of freedom (DOFs) force/torque sensor (Mini 40, ATI Industrial Automation ® ), that revealed a power grasp of about 24 N [4]. Grasp force tests of the "Soft Hand Prosthesis", were performed by means of a force/torque sensor (Nano 25, ATI Industrial Automation ® ) positioned inside a split cylindrical handlebar [5]. A multi-axis dynamometer was also presented with the purpose to evaluate the grip force of human hands in a range between 5 and 250 N. The device consists of three aluminum beams covered by caps to form a cylindrical shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grip performances of the "KIT Prosthetic Hand" were evaluated by using split cylinders with diameters of 31 mm and 49 mm, containing a six degrees of freedom (DOFs) force/torque sensor (Mini 40, ATI Industrial Automation ® ), that revealed a power grasp of about 24 N [4]. Grasp force tests of the "Soft Hand Prosthesis", were performed by means of a force/torque sensor (Nano 25, ATI Industrial Automation ® ) positioned inside a split cylindrical handlebar [5]. A multi-axis dynamometer was also presented with the purpose to evaluate the grip force of human hands in a range between 5 and 250 N. The device consists of three aluminum beams covered by caps to form a cylindrical shape.…”
Section: Introductionmentioning
confidence: 99%
“…Another study proposed an estimation of the grip force by measuring the current absorption of the prosthesis actuator. The current absorbed by the motor is proportional to the torque generated and, in turn, to the tendon traction force and to the gripping force; however, friction must be taken into account [5].…”
Section: Introductionmentioning
confidence: 99%
“…A different approach to providing sensory feedback is based on mechanotactile stimulation, consisting in a force/pressure applied in a different area (the residual limb) from the original stimulus [ 30 ]. An example is an elastic armband connected to two DC motors [ 32 ], which rotate in opposite directions to tighten or loosen the band, in order to help the user adjust the gripping force. Current mechanotactile devices are more cumbersome and heavier than vibrotactile or electrotactile devices, also resulting in higher energy consumption [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…While standard high-level control systems use EMG signals only to reconstruct a position reference, more sophisticated low-level control paradigms, as mechanical impedance control (Hogan, 1984 ) can be used to determine the dynamic relation between manipulator variables, such as end-point position and force, to adapt the system performance to different requirements. It is known that even a simple implementation of this approach, such as the active tuning of the proportional gain ( Kp ) of the motor controller, can strongly modify the performance of a robotic system (e.g., Fu and Santello, 2018 ). This tuning affects both the action velocity, e.g., closing or opening, and the grip rigidity (i.e., hand stiffness).…”
Section: Introductionmentioning
confidence: 99%